E-VTOL AIR TRANSPORT IN THE CZECH REPUBLIC – PUBLIC KNOWLEDGE AND EXPECTATIONS: Public Knowledge and Expectations (Perner's Contacts, 2021)
Vertical take-off and landing aircraft powered by electric propulsion units are considered one of the main areas of future air transport of people or goods over shorter distances. This paper introduces this mode of transport and lists its advantages and disadvantages. The main part is then devoted to a survey of the Czech public's awareness of e-VTOL aircraft and also highlights the expectations people associate with the new mode of transport. To do this, a simplified quantitative research method using a questionnaire survey was used. It was found that the majority of the public is not aware of e-VTOL aircraft, but after the technology was explained, people would be willing to use it if the price of transport was at most 20% higher than conventional modes of (ground) transport.
Keywords: e-VTOL; air transport; public knowledge; urban air mobility; advanced air mobility